2020
DOI: 10.1111/1759-7714.13576
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA LINC00511 plays an oncogenic role in lung adenocarcinoma by regulating PKM2 expression via sponging miR‐625‐5p

Abstract: Background Lung adenocarcinoma (LAC) is the most prominent histological subtype of non‐small cell lung cancer (NSCLC) with a high rate of mortality and metastasis. Accumulating evidence has shown that long non‐coding RNAs (lncRNAs) play malfunctioning roles in the development of human tumors. Hence, this study aimed to determine the biological function of LINC00511 in LAC and to provide a novel diagnostic and therapeutic target for it. Methods LINC00511 expression in LAC tissues and cell lines (H1299 and A549)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…To this end, publicly available Ago2-CLIP data [ 32 ] was analysed to identify miRNAs that interact with LINC00511 and miR-625-5p identified as the top interactor (Fig. 4a ), an observation supported by several recent articles demonstrating that LINC00511 directly sponges miR-625-5p in renal, gastric and lung cancer [ 33 35 ]. To investigate if LINC00511 is functioning to sponge miR-625-5p in melanoma, LINC00511 was knocked down in A2058 cells, as described above, and miR-625-5p expression analysed via miRCURY LNA miRNA PCR Assay.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, publicly available Ago2-CLIP data [ 32 ] was analysed to identify miRNAs that interact with LINC00511 and miR-625-5p identified as the top interactor (Fig. 4a ), an observation supported by several recent articles demonstrating that LINC00511 directly sponges miR-625-5p in renal, gastric and lung cancer [ 33 35 ]. To investigate if LINC00511 is functioning to sponge miR-625-5p in melanoma, LINC00511 was knocked down in A2058 cells, as described above, and miR-625-5p expression analysed via miRCURY LNA miRNA PCR Assay.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that lncRNAs play a vital role in inhibiting oncogenes and preventing the occurrence of malignant tumors ( 8 , 9 ). Several lncRNAs are aberrantly expressed in LUAD, leading to tumor inhibition or carcinogenicity depending on different mechanisms, including sponging and post-transcriptional regulation ( 10 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…In malignant pleural mesothelioma (MPM) (34,35) and thyroid cancer (TC) (36,37), miR-625 was found to be upregulated. It is downregulated in bladder cancer (38), nasopharyngeal carcinoma (NPC) (39), lung cancer (40)(41)(42)(43)(44)(45)(46), HCC (47), cervical cancer (CC) (48,49), osteosarcoma (50), melanoma (51)(52)(53)(54), laryngeal squamous cell carcinoma (LSCC) (55), acute myeloid leukemia (AML) (56), BC (57)(58)(59), glioma (60,61), esophageal cancer (EC) (62)(63)(64), clear cell renal cell carcinoma (65), GC (66)(67)(68)(69)(70), and pancreatic ductal adenocarcinoma (PDAC) (71). In colorectal cancer (CRC), the expression of miR-625 seems to vary, being either high or low.…”
Section: Mir-625 In Cancers Aberrant Expression Of Mir-625 In Cancersmentioning
confidence: 99%
“…Lung adenocarcinoma (LAC) is the most common histological subtype of NSCLC (88). Xue and Yang et al reported that miR-625 was involved in the process by which lncRNAs promoted the progression of LAC (45,46). Interestingly, miR-625 shows obvious antiinflammatory effect in both lung injury model and asthma model, through completely different molecular mechanisms (89,90).…”
Section: Non-small-cell Lung Cancer (Nsclc)mentioning
confidence: 99%
See 1 more Smart Citation